1997
DOI: 10.1017/s0022149x00000717
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations in the infection of a population of Clypeomorus bifasciata (Gastropoda: Prosobranchia) by a digenean microphallid larva in Kuwait Bay

Abstract: The structure and formation of metacercarial cysts in the trematode family Microphallidae Travassos 1920Desiccation survival of populations of the entomopathogenic nematodes Steinernema feltiae and Heterorhabditis megidis from Greece and the UK Preliminary biochemical characterization of faeces from uninfected rats and rats infected with the tapeworm, Hymenolepis diminuta

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Sin embargo, son diversos los factores ambientales que pueden influir sobre la producción y liberación de las cercarias, e.g., pH, incremento de luz y de salinidad, ciclo de mareas (Marcogliese 2001, Mouritsen 2002, Fingerut et al 2003, Koprivnikar & Poulin 2009a. Los registros más frecuentes se refieren al aumento de la producción de cercarias con el aumento de la temperatura, aunque hay considerable variación entre las especies de Digenea, y entre los individuos hospedadores (Meyrowitsch et al 1991, Lo & Lee 1996, Lyholt & Buschmann 1996, Abdul-Salam et al 1997, Cremonte et al 2001, Fried et al 2002, Fredensborg et al 2005, Koprivnikar & Poulin 2009aMorley 2011, Shim et al 2013. El único estudio en Chile del efecto del parasitismo por Digenea sobre el metabolismo de sus hospedadores mostró que los hospedadores parasitados tenían un mayor consumo de oxígeno que los no parasitados (Olmos & George-Nascimento 1997).…”
Section: Introductionunclassified
“…Sin embargo, son diversos los factores ambientales que pueden influir sobre la producción y liberación de las cercarias, e.g., pH, incremento de luz y de salinidad, ciclo de mareas (Marcogliese 2001, Mouritsen 2002, Fingerut et al 2003, Koprivnikar & Poulin 2009a. Los registros más frecuentes se refieren al aumento de la producción de cercarias con el aumento de la temperatura, aunque hay considerable variación entre las especies de Digenea, y entre los individuos hospedadores (Meyrowitsch et al 1991, Lo & Lee 1996, Lyholt & Buschmann 1996, Abdul-Salam et al 1997, Cremonte et al 2001, Fried et al 2002, Fredensborg et al 2005, Koprivnikar & Poulin 2009aMorley 2011, Shim et al 2013. El único estudio en Chile del efecto del parasitismo por Digenea sobre el metabolismo de sus hospedadores mostró que los hospedadores parasitados tenían un mayor consumo de oxígeno que los no parasitados (Olmos & George-Nascimento 1997).…”
Section: Introductionunclassified
“…Host-parasite interactions on the population level have recently come into focus of research on coastal ecosystems (Lauckner 1983, 1984, Jokela & Lively 1995, Curtis 1996, Abdul-Salam et al 1997, Mouritsen 1997. Parasites are recognized as important members of communities influencing abundance and structure of their host populations (Galaktionov & Dobrovolsky 1984, Granovitch 1992, Lafferty 1993 and are included in food chains (Lauckner 1983(Lauckner , 1984.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method does not seem to be suitable for surveying snails, such as C. cingulata and C. bifasciata , infected with other digenean parasites, because the primers used for the retrieval of the complete ITS2 region appear to anneal to highly conservative regions of 5.8S and 28S of most digenetic trematodes (Kralova-Hromadova et al, 2008) and, as such, they amplify the ITS2 region for all digenean parasites infecting the same snail host. It has been reported that the snail intermediate hosts of M. eroliae and P. uca may harbour between 12 (Abdul-Salam et al , 1994; Abdul-Salam et al , 1997; Al-Kandari et al , 2007) and 15 (Abdul-Salam & Sreelatha, 1998) different trematode infections, respectively. Thus it is possible that the digenean-specific primers used in this study to amplify the ITS2 region from M. eroliae and P. uca can also amplify the same region in other trematode species whose DNA sequences are still not available in GenBank and, thus, may contain the Ava II restriction site.…”
Section: Discussionmentioning
confidence: 99%